Assessment of Wildlife Conservation and Educational Visits at University of Ilorin Zoological Garden, Nigeria - Adeola, A. J.; Halidu, S. K.; Sulyman, A.; Adeniji, O. A.; Olaifa, O. P.; Adedeji, A. S. (NIU Journal of Social Sciences, 2022)
University of Ilorin Zoological garden, serves as a tourism destination to both pupils/students and general public; especially during the festive period. However, little study has been done on the assessment of the perception of visitors to wildlife conservation of the zoological garden. The study assessed wildlife conservation and educational visitation to University of Ilorin Zoological Garden. Data obtained through a pre-tested questionnaire and was analyzed using descriptive statistics. The findings revealed that 58.0% of the respondents were females and 42.0% were males. The highest age group lies between 25-34 years old.69% of the visitors are from Kwara State, 28% from others state and 3% are foreigners. Students were the highest category (66%) of visitors while 29% represent civil servants. Majority of the respondents had visited other zoological gardens; and the major reason for the visit was for excursion and recreation purposes. 38% got information about the place from their various school, follows by family with 31% and the least are through media(4%). Result further shows that 75% of the respondents were satisfied with the development of Zoological garden while only 7% are indifferent; and 92% of the respondents are ready to visit the Zoological garden again. 57% of the respondents were aware of wildlife conservation through their school, 33% from friends and 10% from family members. University of Ilorin Zoological garden is a good recreation centre that needs to be publicized in the mass media, since the level of awareness from other sources other than from school and friends ranked the lowest. Keyword: Wildlife, Conservation, Zoological garden, Ilorin